High Expression Levels of SIGLEC9 Indicate Poor Outcomes of Glioma and Correlate With Immune Cell Infiltration - Xu, Heng; Feng, Yanyan; Kong, Weijia; Wang, Hesong; Feng, Yuyin; Zhen, Jianhua; Tian, Lichun; Yuan, Kai (Frontiers in Oncology, 2022)
Objective This study aimed to investigate the diagnostic value and underlying mechanisms of sialic acid-binding Ig-like lectin 9 (SIGLEC9) in gliomas. Patients and Methods The Cancer Genome Atlas (TCGA) and the Chinese Glioma Genome Atlas (CGGA) databases were used to analyze the association of SIGLEC9 expression levels with tumor stages and survival probability. Immunohistochemical staining of SIGLEC9 and survival analysis were performed in 177 glioma patients. Furthermore, related mechanisms were discovered about SIGLEC9 in glioma tumorigenesis, and we reveal how SIGLEC9 functions in macrophages through single-cell analysis. Results TCGA and CGGA databases indicated that patients with high SIGLEC9 expression manifested a significantly shorter survival probability than those with low SIGLEC9 expression. SIGLEC9 was upregulated significantly in malignant pathological types, such as grade III, grade IV, mesenchymal subtype, and isocitrate dehydrogenase wild-type gliomas. The immunohistochemical staining of tissue sections from 177 glioma patients showed that high-SIGLEC9-expression patients manifested a significantly shorter survival probability than low-SIGLEC9-expression patients with age ≧60 years, grade IV, glioblastoma multiforme, alpha thalassemia/intellectual disability syndrome X-linked loss, and without radiotherapy or chemotherapy. Furthermore, the SIGLEC9 expression level was positively correlated with myeloid-derived suppressor cell infiltration and neutrophil activation. The SIGLEC9 expression was also positively correlated with major immune checkpoints, such as LAIR1, HAVCR2, CD86, and LGALS9. Through single-cell analysis, we found that the SIGLEC9 gene is related to the ability of macrophages to process antigens and the proliferation of macrophages. Conclusion These findings suggested that SIGLEC9 is a diagnostic marker of poor outcomes in glioma and might serve as a potential immunotherapy target for glioma patients in the future.